Screening of antimicrobial activities in the leaves of wild ficus deltoidea gold line / Nurhidayu Jamaludin - Jamaludin, Nurhidayu (2007)
The goals of this work were to obtained the solvent extraction (n-hexane, chloroform and methanol), to conduct pyhtochemical screening test and to determine antimicrobial activities in the leaves of Ficus deltoidea. The three solvent extractions with different concentrations were tested by using disc diffusion method against Aspergillus niger, Candida albicans, Bacillus subtiltis, Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus and Streptococcus feacalis. The results of phytochemical screening indicated that the leaves of Ficus deltoidea contained flavanoids, terpenes and saponins. For antimicrobial activities, all solvent extractions inhibited the growth of bacteria especially B.subtilis, E.coli, P.aeruginosa, and S.aureus but fungi (A.niger and C.albicans) were resistant to the all the extracts.